Oasis agriculture revitalization and carbon sequestration for climate-resilient communities - Dhawi, Faten; Aleidan, Megbel M. (Frontiers in Agronomy, 2024)
Revitalizing oasis agriculture, an age-old human endeavor, has historically played a crucial role in sustaining biodiversity and ecosystems in arid regions. Nevertheless, this enduring practice now faces contemporary challenges, including global warming, water scarcity, soil erosion, and negative human activities associated with urbanization. This comprehensive review delves into diverse literature across disciplines, covering topics such as water conservation, biodiversity restoration, agroforestry, and Oasis Holistic Management, with the aim of addressing these challenges. The analysis strongly advocates for the urgent adoption of sustainable practices, including precision irrigation, polyculture, organic farming, agroforestry, and community-based initiatives, to ensure the survival of oasis agriculture and foster long-term environmental and social responsibility. The study underscores the imperative need for the development of “comprehensive, flexible, and forward-looking management strategies” to guide the sustainable revival of oasis farming. By consolidating information from various studies, it lays the groundwork for informed decision-making and policy formulation. As part of revitalizing the oasis agricultural ecosystem and addressing the global climate crisis, we propose a noninvasive tool for assessing carbon sequestration effectiveness based on tree specifications. Recognizing the pivotal role of vegetation in mitigating the ecological impact and facing global crises, we explored parameters influencing plant carbon sequestration, including biomass production, growth rate, longevity, root structure, leaf structure, and average temperature tolerance.